Prescriptive model for knowledge management in doctoral programs - de la Vega Hernández, Iván Manuel; Rodriguez-Montoya, Cristobal; Yáber-Oltra, Guilllermo E.O. (Interciencia Association, 2017)
The expansion of intellectual capital, fueled by the generation of new knowledge, contributes to an increasing wellbeing of society. However, the gap between Latin American and other countries, due to the smaller quantity of scientific papers published and patents filed, presents a problem that requires urgent attention. The doctoral programs offered by our universities, important knowledge producers in our countries, could increase their intellectual production by using knowledge management (KM), in an analogous way to companies that have adopted it. In that sense, the goal of this research is to simplify the adoption of KM processes, formulating a prescriptive model developed from a theoretical and qualitative analysis of the relevant literature, contrasted in the authors' own discussions, from a perspective based on their combined experience as participants and administrators of doctoral programs. It is expected that the use of KM systems, based on the guidelines of the proposed model, will have a positive impact, implying an increased intellectual production of doctoral programs.
Keywords: Intellectual capital; Knowledge management; Doctoral programs; https://purl.org/pe-repo/ocde/ford#5.02.00